Transient hydrodynamic patterns of high Weber number ethanol droplet train impingement on heated glass substrate - Kanbur, Baris Burak (2022)
The transition of high-speed and high-frequency ethanol droplet train impingement on the glass substrate is investigated according to the surface temperature range of 80∘C-230∘C along 50 milliseconds. The Weber numbers of 1145, 1400, and 2067 are obtained using three different pinhole diameters in the droplet generator nozzle. Steady-state spreading diameter conditions are not reached along 50 milliseconds for three different Weber numbers. The spreading diameter trends depend on the thermal balance between the supplied liquid ethanol via the nozzle and the ethanol consumption from the glass surface via evaporation rate and splashing. Thus, the spreading diameter increases with increments in the Weber number while decreases by the rising of the glass surface temperature by means of higher surface energy levels. The boiling, transition, and post-transition regimes are observed. Crown rim formation, nucleation bubbles, and sluggish columns are observed around the droplet impact area within the boiling regime that has greater spreading diameters than the following regimes. The transition region is defined by observing splashing angles that decrease from the surface temperature of 170∘C to 200∘C. The Leidenfrost point is reached between 200∘C and 230∘C.